A Case of Successful Rehabilitation for Controlling Chronic Pain Following Osteonecrosis of the Femoral Head in a Young Adult Cancer Survivor - Aoyama, Tomoki; Matsuoka, Mari (Cureus, 2024)
A 26-year-old woman previously treated for acute lymphoblastic leukemia (ALL) 14 years ago faced challenges in managing chronic pain resulting from right femoral head necrosis, a complication of her earlier ALL treatment. Ultimately, the persistent chronic pain was successfully treated via a comprehensive rehabilitation approach. The patient presented with hip contractures, muscle weakness, and reduced endurance without evident arthropathic changes or inflammatory findings in the femoral head. Active physiotherapy was implemented with the primary objective of increasing her social activity. This therapeutic intervention effectively managed the severe pain without the necessity for analgesic drugs, leading to a significant improvement in the patient's social activity. Recognizing the adolescent and young adult age group as a critical phase of physical, psychological, and social development, cancer survivors within this age group require multimodal care. This study highlights the role of stepwise rehabilitation treatments involving stretching, muscle strengthening, and endurance training, particularly in challenging cases of chronic pain. Post-treatment interviews revealed that successful experiences in each movement contributed to increased self-efficacy and promoted not only the control of chronic pain but also fostered improvements in social activities.